Didactic strategies in the thesis advising to develop research competencies: perspectives of teachers and students - Tapullima-Mori, Calixto (2024)
Introduction: Introduction: Thesis advising is an essential component in academic training, where students embark on the task of researching and contributing to knowledge in their field of study, for this it requires specific competencias on research and tools that contribute to its development. Objective: The objective of this study was to analyze the use of teaching strategies by professors in the thesis advising process to develop research competencies in students in the last cycles of higher education. Method: An exploratory phenomenological qualitative design was followed, and semistructured interviews were applied to three research experts and three students from the Faculty of Psychology, belonging to a private university in the city of Tarapoto-Peru, who were selected through purposive convenience sampling. Results: It was understood that (a) the didactic strategies that are applied in teaching and learning for the achievement of academic objectives are collaborative work, case studies, the use of audiovisual resources, teamwork; (b) research competencies are defined as a set of skills, skills and attitudes needed to carry out research and thesis projects; In addition, (c) it is necessary to know how to formulate problems, hypothesize, master statistical software and argue the results efficiently; (d) it is important to emphasize the capacity for the analysis of methodological coherence and the use of bibliographic managers. Discussion: The identified strategies allow the acquisition of knowledge for the development of research competencies, however, to achieve greater functionality, students must demonstrate willingness and commitment.